EFFECT OF OMEGA 3 ON CAO AND P2O5 AS HYDROXHAPATITE CONSTITUENTS IN DENTAL MICE (MUS MUSCULUS) - Permatasari, Viyata Rafikha; Christiono, Sandy; Mujayanto, Rochman (Jurnal Medali, 2024)
Background: Omega has many benefits for the human body, such as acting as an anti-inflammatory, strengthening bones and teeth and helping the absorption of calcium in the body. Increased absorption of calcium so that the formation of bones and teeth will be more optimal. Omega 3 cannot be produced by the body so it needs external intake such as supplements containing omega 3. Pregnant women need this omega 3 intake to improve nutrition for the fetus and minimize caries and hypoplasia in children. Purpose: to determine the effect of omega 3 on CaO and P2O5 as hydroxyapatite constituents in the teeth of mice (Mus musculus). Method: This experimental study was conducted with a post test only control group design with a sample of 16 teeth. The groups were divided into two, namely the treatment of giving omega 3 and the control of distilled water in pregnant mice. Pregnant mice were given omega 3 during pregnancy and birth. Omega 3 supplements use a dose of 0.001 ml. Statistical tests were carried out using an independent t-test. Test CaO and P2O5 as hydroxyapatite constituents in the teeth of mice using SEM. Observation of email brute force results using SEM. Results: In this study there was a significant difference p